AN ANALYSIS OF STUDENTS’ SPEAKING ACTIVITY ON ENGLISH DAY - Mahiesta, Syeraivy; Susilawati, Endang; Rosnija, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract:. This research was conducted for the purpose of analyzing the students’ speaking activity on English Day at SMA Taruna Bumi Khatulistiwa in academic year 2012/2013, the program is applied in two days in a week, Tuesday and Thursday. It is organized by students Organization (OSIS). In this program, students are obligated to use English in for any communication purposes.In this research the writer applied descriptive method as the technique of collecting data. The sample of this research was 10th grade 30 students, 11th grade 24 students, grade 12th 18 students. In collecting the data, the researcher provided a set of questionnaire statements with 25 test items and she also applied  observation the use of English by the students on English day for any communication purposes. Based on the questionnaire Students have many problems in Linguistics and psychological. Meanwhile from the observation, writer saw that English day can help the students to practice their English not only in the classroom, but also outside the classroom. Most of the students communicated in English on English day programs. Therefore, it can concluded that English day program can facilitate the students to develop their speaking ability although some linguistic and psycholinguistic were still occurring, Keywords: Speaking Activity, English Day Program Abstrak: Penelitian ini dilakukan dengan tujuan untuk menganalisi aktivitas berbicara siswa menggunakan Bahasa Inggris dalam Program English Day di SMA Taruna Bumi Khatulistiwa tahun pelajaran 2012/2013 yang diterapkan 2 hari dalam seminggu, yaitu hari Selasa dan Kamis. Program ini merupaka program yang dikelola oleh OSIS  Dalam program siswa diwajbkan menggunakan Bahasa Inggris dalam semua kegiatan. Dalam penelitian ini penulis menerapkan metode deskripsi. Sample dalam penelitian ini adalah 30 siswa kelas X, 24 orang siswa kelas XI dan 28 siswa kelas XII. Pada pengumpulan data, penulis menggunakan questioner dengan 30 pernyataan dan melakukan observasi Berdasarkan questioner siswa banyak mengalami masalah yang berkenaan  dengan masalah Kebahasaan dan masalah Psikologis. Sementara itu  berdasarkan observasi penulis menyimpulkan Program English Day dapat menunjang siswa untuk berbicara menggunaka Bahasa Inggris baik di dalam kelas maupun diluar kelas. Dengan demikian dapat disimpulkan bahwa Program English Day dapat meningkatkan kemampuan dan aktivitas siswa dalam menggunakan Bahasa Inggris meskipun masih terdapat kendala dengan masalah-masalah yang berkaitan dengan masalah kebahasaan dan masalah psikologis. Kata Kunci: Aktivitas Berbicara, Program English Day